The Expression of Murine Double Minute 2 (MDM2) on Helicobacter pylori-Infected Intestinal Metaplasia and Gastric Cancer - Nakajima, Noriko (the Society for Free Radical Research Japan, 2009)
The overexpression of murine double minute 2 (MDM2) is found in several human tumors, and increased expression of MDM2 inactivates the apoptotic and cell cycle arrest function of p53. Interleukin-16 (IL-16) is a pleiotrophic cytokine and the properties of IL-16 suggest that it involve in the pathophysiological process of chronic inflammatory diseases. In this study, we investigated the expression of MDM2 in intestinal metaplasia and gastric cancer as well as the effect of H. pylori infection and IL-16 on epithelial cell proliferation and MDM2 expression in gastric cells in vitro. The expression of MDM2 on gastric biopsies was studied immunohistochemistry. AGS cells were incubated with a combination of IL-16 and Helicobacter pylori (H. pylori). Gastric epithelial cell proliferation was studied by BrdU uptake and the expressions of MDM2 were studied by ELISA. There was no significant difference on the expression of MDM2 between with and without H. pylori infected chronic gastritis. In H. pylori infected gastric mucosa; the MDM2 expression was higher on intestinal metaplasia and gastric cancer than chronic gastritis. IL-16 administration was increased MDM2 expression and cell proliferation on AGS cells, which was decreased by H. pylori infection. In conclusion, the expression of MDM2 in long-term H. pylori infected gastric mucosa may indicate a risk for carcinogenesis. IL-16 secretion in H. pylori infected mucosa is one of the factors for gastric cancer. The expression of MDM2 on mucosa can be a mediator for gastric cancer.